PENGARUH KUALITAS SDM, SIPKD, AUDIT INTERNAL TERHADAP AKUNTABILITAS LAPORAN KEUANGAN PEMPROV BALI - Desak Made Deviyanti; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2022)
Central and local governments have implemented public accountability in response to the growing public demand for good local government. Human resource quality, regional financial information systems (SIPKD), and the role of internal audit are all examined in this study to see if they affect regional financial reporting in Bali. The entire Bali Provincial Government Work Unit was used as the study's sample. Purposive sampling and multiple linear regression analysis techniques were used to select 140 participants for this study. This study found that the Quality of Human Resources had a positive and statistically significant impact on the Regional Financial Report Accountability metric. For the Regional Financial Report Accountability variable, the Regional Financial Management Information System (SIPKD) had a positive and statistically significant impact An important contribution to the Accountability of Regional Financial Statements was made by Internal Audit. Regulations and policies relating to the accountability of financial statements can take into account the findings of this research.